Síntese regiosseletiva de Dideoxinucleosídeos e 3(5)-Trifluormetil-1H-pirazóis de interesse farmacológico - Lobo, Marcio Marçal (2015)
This work reports the synthesis of a series of 29 new 1-(3-aryl-4,5-dihydroisoxazol-5-yl)methyl-4-trihalomethylpyrimidin-2(1H)-ones which have high pharmacological interest, since they are similar to natural and synthetic nucleosides. These compounds were obtained from 1,3-dippolar cycloaddition reaction between the 1-allyl-(6-aryl)-4-trihalomethylpyrimidin-2(1H)-ones and different benzonitrile oxides, obtained from the selected oximes of general formula ArCH=NOH (where Ar = Ph, 4-FC6H4, 2-MeC6H4, 4-MeC6H4, 2-MeOC6H4, 4-MeOC6H4, styryl, 2-OHC6H4 e 4-OHC6H4). The reaction conditions employed were highly regioselective, because it was observed the formation of only 3,5-substituted isomer by both NMR spectral analysis and X-ray diffractometry. The compounds were obtained in good yields (58 99%) and were purified from recrystallization or by column chromatography on silica gel. Some the obtained compounds showed antineoplastic activity in vitro against different tumor cell lines. Additionally, three new N3-substituted pyrimidinic dideoxynucleoside analogues were prepared, which were obtained in good yields (88 97%) from the reaction of N-allyl-2-methylthiopyrimidin-4(3H)-one and some of the benzonitrile oxides mentioned above. The reactions for the formation of N3-substituted nucleoside still require optimization. This thesis also described the regiochemisty controled synthesis of two series of pyrazoles, named 5(3)-aryl-3(5)-trifluoromethyl-(1H-pyrazol-1-yl)benzenesulfonamides, structural analogues of Celecoxib (14 examples), where aryl = Ph, 4-FC6H4, 4-MeC6H4, 4-MeOC6H4, 4-ClC6H4, 4-BrC6H4, furan-2-yl, from the cyclocondensation reaction between 4-aryl-1,1,1-trifluoromethyl-4-methoxy-3-buten-2-ones and 4-hydrazinobenzenosulfonamide hydrochloride. The isolation of either isomer depended on the initial pH medium, where the alkaline pH favored the isolation of the 1,5-substituted isomer at yields of 73 99% and the reaction conducted in acid pH favored the isolation of the 1,3-substituted isomer, with yields of 77 94%. This study also allowed the isolation and spectroscopic characterization of a novel series of 3-aryl(heteroaryl)-5-hydroxy-5-trifluoromethyl-(1H-pyrazol-1-yl)benzenesulfonamides (7 examples) in yields of 75 97% with interesting anti-inflammatory and antinociceptive activities in vivo.